2019
DOI: 10.1684/abc.2019.1433
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinico-biological, therapeutic and evolutionary aspects of β-thalassemia in Morocco

Abstract: Objectifs : Les thalassémies sont la conséquence d'un déséquilibre de synthèse entre les chaînes ␣ et ␤ de l'hémoglobine. Ce sont des anémies hémolytiques héréditaires, qui présentent un problème de santé publique vue leur fréquence et les difficultés de leur prise en charge. L'objectif de ce travail est d'étudier le profil épidémiologique, clinico-biologique, thérapeutique et évolutif des patients thalassémiques au Maroc. Méthodes : Nous rapportons les résultats d'une étude rétrospective, multicentrique, port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Consanguinity therefore plays an important role in the occurrence of familial forms, with variable genotypes, as shown by our clinical cases 1 and 2, where three cases were found, two of them alive and the older brother probably dead from beta-thalassaemia major. Other authors, notably Barouni [12,13,14,15]. Barouni M et al also found in their study that 37.1% of thalassaemia patients had at least one brother or sister affected by the same disease [12].…”
Section: Clinical Diagnosismentioning
confidence: 81%
“…Consanguinity therefore plays an important role in the occurrence of familial forms, with variable genotypes, as shown by our clinical cases 1 and 2, where three cases were found, two of them alive and the older brother probably dead from beta-thalassaemia major. Other authors, notably Barouni [12,13,14,15]. Barouni M et al also found in their study that 37.1% of thalassaemia patients had at least one brother or sister affected by the same disease [12].…”
Section: Clinical Diagnosismentioning
confidence: 81%